Niche Diplomacy Indonesia melalui Forum Negara Kepulauan dan Negara Pulau: Meningkatkan Kebijakan Luar Negeri Maritim - Hidayatullah, Nur Luthfi (Jurusan Ilmu Hubungan Internasional, 2026)
This study aims to describe Indonesia’s niche diplomacy during its chairmanship of the Archipelagic and Island States (AIS) forum in 2023. This research uses descriptive qualitative method by utilizing the niche diplomacy concept to describe Indonesia’s maritime foreign policy as a middle power. The result shows that Indonesia practiced niche diplomacy during its chairmanship of the AIS Forum in 2023 by enhancing its maritime foreign policy in three ways. Firstly, securing niche in maritime foreign policy by addressing the archipelagic and island states’ environmental problems, encouraging AIS participants to sign the Manado Declaration, and providing funding to establish a secretariat and support AIS Forum’s programs. Secondly, Indonesia obtains national interest by selecting the AIS Forum’s key issues in line with the Global Maritime Fulcrum’s pillars, conducting domestic policies to support the AIS Forum, and encouraging other states to do the same. Thirdly, contributing towards international agenda by striving to reach the Sustainable Development Goals 14, and preparing the AIS Forum to become an international organization. Hence, a middle power conducting niche diplomacy needs to select a low political issue to address through its domestic and foreign policies to gain national interest and benefit other states as well.